Issues in ELT Pedagogy: Working with the 21st Century Student - Saroli, Anna (CIEX JOURNAL, 2017)
It can be difficult to keep abreast of the rapid changes in language pedagogy. This workshop will start with an overview of some of the central theories and issues in English language teaching. After a discussion of how what we do as teachers has evolved to accommodate student needs and expectations, we will break into small groups to develop some strategies for supporting students with different learning styles and discuss how to incorporate learning opportunities and strategies in the classroom.